Analysis of Perception Theory: Normalization of Turkiye - Israel Relations in the Erdogan Era - Indraningtyas; Sugito (Universitas Muhammadiyah Yogyakarta, 2023)
This article begins with the issue of restoring diplomatic relations between Turkey and Israel after previously being terminated by Erdogan due to the Mavi Marmara ship incident. This issue is a problem because Erdogan seems inconsistent in implementing his policies. Therefore, this article tries to explain foreign policy changes using a constructivist approach that focuses on individuals and uses Perception Theory formulated by Holsti as an analytical tool. This research found that the normalization of relations between Turkey and Israel was caused by a change in Erdogan's perception of looking at Turkey because of his nationalism, where there is a desire and interest to make Turkey a big, advanced, and prosperous country. Apart from that, the values of nationalism that Erdogan adheres to also influence Erdogan's views so that he considers severing or freezing relations with Israel to be an obstacle to Turkey achieving progress and a threat. Therefore, for the sake of progress and protection of the homeland, Erdogan adopted a normalization policy. Most previous research analyzes this problem using the perspective of the state as a political actor, and not many studies specifically focus on Erdogan as an individual in making decisions. Therefore, this research tries to explore this problem from a different perspective, using the perspective and theory of individuals as political actor as well as policies based on constructivist values, where research from this perspective is still rarely discussed.